Effects of Agaricus Blazei Extract Plus Lactoferrin or Lactoferrin Alone on Tumor Growth and UFT-Induced Adverse Reactions in Sarcoma 180- or Highly Metastatic Osteosarcoma LM8-Bearing Mice - Kimura, Yoshiyuki; Sumiyoshi, Maho; Usuki, Kou-ichi (Natural Products Journal, The, 2015)
Objective: The protective effects of Agaricus blazei extract (ABE) and lactoferrin (LF) on 5-FU derivative-induced adverse reactions remain unclear. We examined the effects of a combination of ABE and LF on tumor growth and metastasis, as well as UFT-induced adverse reactions using a highly metastatic model in osteosarcoma LM8-bearing mice. Methods: In this study, we examined the antitumor activity and adverse reactions, such as myelotoxicity and body-weight loss, of the cancer chemotherapy drug a 5-FU derivative, UFT (50 mg/kg) when given with ABE (9:1, w/w; 0.43 or 1.4 g/kg, twice daily) and LF (100 or 300 mg/kg, twice daily) in sarcoma 180- or osteosarcoma LM8-bearing mice. Key Findings: ABE-LF or LF inhibited tumor growth and metastasis to the lung without causing adverse reactions in LM8-bearing mice. ABE-LF or LF prevented the reductions induced in the number of red blood cells, leukocytes, and platelets, as well as hemoglobin levels and the hematocrit percentage by UFT without affecting the antitumor and antimetastatic effects of UFT. Since neither ABE nor LF inhibited the phosphorylation of 5-FU, the protective effects of ABE-LF or LF on UFT-induced myelotoxicity (reductions in red blood cell numbers) could not be attributed to the inhibition of 5-FU phosphorylation. Conclusion: These results suggest that the protective effects of LF and/or ABE-LF on the adverse events induced by UFT toxicity such as myelotoxicity may be partly due to the myelopoietic actions of LF.
Keywords: Myelotoxicity